Analisis Budaya Literasi Siswa SD Negeri 04 IX Korong Kota Solok - Ariani, Dewi (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2021)
This study aims to determine the analysis of literacy culture owned by students of SD Negeri 04 X Korong Kota Solok. This type of research is a quantitative study using descriptive methods. Sources of data used are primary data and secondary data. Data collection techniques in this study using observation, questionnaires, interviews and documentation. The population of this study were students of SD Negeri 04 IX Korong Kota Solok, with a total sample of 38 people, consisting of all students in Class V. This was taken by purposive sampling due to the limitations of the authors in taking samples during the pandemic. The data analysis method used is the test instrument, namely the validity test and reliability test. Quantitative data processing is accompanied by analysis. The results showed (1) books that most elementary school students like are story books, can be novels or other reading material, (2) the time used to read, on average is 25 minutes per day. This is presumably because students are also involved in other activities after school, such as helping their parents to work, (3) The reason for reading this Class V elementary school student, on average is dominated by 34%, likes reading, 26% does not like reading because it is boring, 26% caused by playing a lot. The rest is caused by not having time to read, prefer to watch and there are no good books according to them that make them interested in reading.